An?lise de efeitos n?o-lineares em fibras ?pticas monomodo - Miranda, Tha?ssa Dela L?bera (2011)
Optical fibers networks arouse great interest for allowing transmission of large amounts of information into optical links in long distances with a few number of repeaters. The bandwidth determines the maximum modulation rate and relates to the distance specified xv for eacha link. There are direct influences of some phenomena in the systems limitations wich are associated with power in the optical fiber core. Among these there are the stimulated Brillouin scattering, stimulated Raman scattering and Kerr effect. The latter one describes a change in refractive index that generates self-phase modulation, cross-phase modulation and four-wave mixing. The effects are mainly present in single-mode fiber transmission medium and at large capacity links. In this work, we will present the causes of these phenomena and their influences in optical communication.